Gemstones of eastern Kazakhstan - Chlachula, Jiri (Geologos, 2020)
An overview is presented of gemstones from eastern Kazakhstan in terms of their geographical distribution, geological provenance and genesis, gemmological characteristics, historical use and current applications. Locally occurring precious, semi-precious and decorative stones were extracted and traded along the northern part of the Silk Road that traversed the area in earlier historical times. Currently, non-metallic minerals, which largely originate from mafic igneous and metamorphic bodies of the Altay and Kalba Mountains of Kazakhstan, still are insufficiently known and exploited industrially only marginally. For the present study, selected depositories of coloured stones at the Mineralogy Museum of the East Kazakhstan State Technical University were used, supplemented by the newly collected material during personal fieldwork in the southern Altay between 2005 and 2015. Standard documentation of the gemstones selected is provided, alongside with their known occurrence sites and an evaluation of the perspective gemstone-bearing deposits with respect to regional morphostructural bedrock characteristics. The most precious gemstones include topaz, corundum (sapphire and ruby), beryl (emerald and aquamarine), coloured tourmalines, agates as well as diamonds. Despite the great variety, the majority of these traditionally most valued stones are currently commercially not viable, unlike high-quality decorative stones.